Study on the acceptance, complications and continuation rate of post-partum family planning using the post placental intrauterine contraceptive device among women delivering at a tertiary care hospital - Gujju, Rajya Lakshmi Bai; Prasad, Usha; Prasad, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Post placental intrauterine contraceptive device use in India showed that most women were satisfied with their choice of immediate insertion of an IUCD and the rates of complications were relatively low. The large proportion of women accepting the method to limit future childbearing indicates the important place post placental IUCD hold. This study was done to evaluate the acceptance of intrauterine contraceptive device as an immediate family planning method following delivery. The complications associated with it were identified and continuation rates were assessed. Methods: Women admitted for delivery in a tertiary care hospital were included in the study. Only women who fulfilled the medical eligibility criteria were included in the study. Results: A total of 4209 women were counseled of which 780 (18.5%) women accepted the method, 3429 declined. Out of the 780 cases, 764 came for follow up, and 16 were lost to follow up, spontaneous expulsion was seen in 2 (0.2%) cases, removal was done on request in 1 case and continuation was seen in 761 (97.56%) women. Conclusions: The Post placental intrauterine contraceptive device is safe to insert immediately after delivery. It has good acceptance with minimal expulsion and very high continuation rates.